Study of a Transmission Problem with Friction Law and Increasing Continuous Terms in a Thin Layer - Yasmina Kadri; Aissa Benseghir; Salah Boulaaras; Hamid Benseridi; Mourad Dilmi (Mathematics, 2023)
The aim of this paper is to establish the asymptotic analysis of nonlinear boundary value problems. The non-stationary motion is given by the elastic constructive law. The contact is described with a version of Tresca’s law of friction. A variational formulation of the model, in the form of a coupled system for the displacements and the nonlinear source terms, is derived. The existence of a unique weak solution of the model is established. We also give the problem in transpose form, and we demonstrate different estimates of the displacement and of the source term independently of the small parameter. The main corresponding convergence results are stated in the different theorems of the last section.